KEBIASAAN HYGIENE REMAJA MELAKUKAN PENCEGAHAN PENYAKIT SKABIES DI PESANTREN AL FAJAR KECAMATAN RUMBAI PEKANBARU - KN, Tri Siwi; Norlita, Wiwik (Sistem Informasi, 2018)
Scabies is a common skin disease in tropical countries that are endemic. Scabies prevalence worldwide is reported to be about 300 million cases of year. Indonesia has a prevalence of scabies in 2016 of 4.60-12.9 percent. Based on reports from policlinic pesantren Darel Hikmah Pekanbaru, many santri who experience scabies disease in recent years. In 2009 there were 98 cases and in 2010 it increased to 115 cases. Al Fajar Orphanage is one of the communities that are vulnerable to the incidence of scabies diseases. In the last two years there have been 9 cases of skabies in the santri in the orphanage. This study aims to find out how the habit of teenage hygiene to prevent scabies at Al-Fajar Orphanage Muara Fajar Village, Rumbai District. This research use descriptive with junlah sampel 30 responden. Methods of data collection using questionnaires and. The results of the questionnaire showed that most adolescents had poor hygiene habits of 17 respondents (56.7 percent) with mean <12 and adolescents with good hygiene habits of 13 respondents (43.33 percent) with mean â¥ 12. Based on this research, it can be concluded that the habit of teenage hygiene in preventing scabies disease is still very need to be improved and require more intensive attention from pesantren teacher so that it can reduce the incidence of scabies disease in Al Fajar orphanage.